Women and self-managed habitat production (REVISTA NODO, 2020)
In this paper, we explore the relationship between self-managed habitat production and changes in women’s life. Our study is based on the experience of the cooperatives “La Fábrica” and “El Molino” cooperatives, of the Movement of Occupants and Tenants of the city of Buenos Aires Argentina. The analysis is based on fieldwork-based on participant observation, ethnographic interviews, and a specific survey conducted in 2018. Throughout the paper, the various ways in which the participation of women in collective decision-making bodies that have a significant impact on their habitat through self-management are highlighted. We conclude that this process enables tendencies of delocalization as part of the resignation of daily life and associated with a value of the collective and the “common”.
Keywords: gender relationships; women; city; selfmanagement urbanism; patriarchy